Kesehatan Mental Mahasiswa Ditinjau dari Religiusitas dan Kebermaknaan Hidup - Baidi Bukhori (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This research aimed to investigate correlation among religiousity, life meaning and student’s mental health. Hypotheses proposed there’s positive correlation among those variables. Subjects were 127 students of Da’wah Faculty of IAIN Walisongo and assigned proportional random sampling technique. Three scales were used to collect data, among those were religiousity scale, life-meaning scale and mental helath scale. Multiple regression was used to test the hypotheses. This research found that there’s positive correlation among religiousity, life-meaning and students mental helath. religiousity, life-meaning donate 57,2 % for students mental helath.Keywords: Religiousity, life meaning, and mental health